"Merdeka"! and the dynamics of extreme violence; The first year of the Indonesian Revolution through the eyes of three Dutch journalists - van 't Veer, Coen (Wacana, Journal of the Humanities of Indonesia, 2024)
In the first year after World War II, there was a power vacuum in Indonesia. The Indonesians had declared their independence. The Allies had assigned the administration of the former Dutch colony to the British. The Dutch thought they could continue their colonial ambitions. It was a year of utter chaos and extreme violence. While most Dutch journalists remained in Jakarta, three went to the war zones: two of them as reporters and the other as a soldier. The analysis of three texts on the first year of the Indonesian War of Independence by Dutch eyewitnesses shows the importance of subjecting them to closer scrutiny. In the massive focus on the violence in the Indonesian freedom struggle, literary texts of this kind are too often not taken into consideration, even though they are crucial to gaining an insight into the thinking about this war at that time. Because of their hybrid nature, this type of text is pre-eminent in revealing the tension between clashing conceptions, realities, and truths.